Exit management - Booth, Naomi (Great Britain : Dead Ink, 2020)
"At minus five degrees, even the densest blood materials start to turn: the beginnings of a human heart will still into black ice. Callum has been given an opportunity: Jozsef's house is the perfect place to live - plenty of room, a sought-after London location and filled with priceless works of art. All that Jozsef asks in return is for some company while he's ill and the promise that if it all gets too much, someone will be there to help him at the end. It's fortunate then, when Callum meets Lauren who works in Human Resources and specialises in getting rid of people. Jozsef welcomes them both inside, and so begins a deadly spiral of violence. Pushed ever onwards by the poison of ambition, and haunted by losses from the past, these characters are drawn together in a catastrophe of endings. Naomi Booth's second novel is a groundbreaking dissection of class, xenophobia and compassion. Exit Management will seize you in its cold hands and show you the dark heart within us all."--Provided by publisher.
Includes bibliographical references.
Keywords: Roommates -- Fiction; Terminally ill -- Fiction; Murder -- Planning -- Fiction; Ambition -- Fiction; Choice (Psychology) -- Fiction; London (England) -- Fiction; Great Britain -- Social conditions -- 21st century -- Fiction